A review of injectable materials in the endoscopic treatment of vesicoureteral reflux - (:unkn) unknown (My University, 1996)
Endoscopic treatment of Vesicoureteral Reflux (VUR) has obvious advantages when compared with open surgery. However, the ideal substance for injection is still not found. An ideal material should have no carcinogenic effect, should not migrate, be free of immunologic reactions, should not be absorbed so that it can preserve its volume after injection and cause a limited local tissue reaction in order to strength its mass effect. Although very high success rates are achieved with Polytetrafluoroethylene (PTFE) both in high grade primary and secondary VUR, it does not seem to be a suitable material for the treatment of VUR in children since it migrates and long term effects are not known. Collagen does not migrate, but it is less effective in the treatment of high grade and secondary VUR because it loses its volume by time. Autologous fat has been found completely unsuccessful in VUR, since more than half of it is absorbed and does not cause granulomatous reaction which is necessary for the posterior support of the terminal ureter. PDMS is a new inert agent with a greater particle size than PTFE and theoretically does not migrate. Early results with PDMS are encouraging but it has been suggested that it carries the potential risk of collagen disease in the long term. In conclusion, urologic world still looks forward for an ideal material for the endoscopic treatment of VUR in children.
Keywords: Endoscopic treatment; Injectable materials; Vesicoureteral reflux